(3Mb GdJdGhI (B:s (3cJGH efgLj JWHjbj jYJeO CUhd JOQjS GdJLhjO aj JYde JdGhI GdbQBf hJYdjeg Ydi QhGjI MaU Yf YGUe hHMGTjI GdcJGH GdbhGYO GdJj jNGda ajgG MaUG cd ef GdQhGI bGdhf hhQT hGdOhQj (B/s - (3YKeGf, MSfj TjNs ((3LOI (B- (3GdeedcI GdYQHjI GdSYhOjI (B:s (3ecI GdecQeI (B- (3GdeedcI GdYQHjI GdSYhOjI (B:s (3OGQ GdefGQI ddfTQ hGdJhRjY ,s, 1994)
(3jJfGhd cJGH (B((3Mb GdJdGhI(B) (3hGdPj bGe HJCdjag MSfi TjN YKeGf, ehVhY (B((3GdbQGAGJ(B) (3gPG GdcJGH hVYg eUfag aj GdJdGhI eJHYG ajg WQjbI efgLjI JYdjejI gGOaI, YHQ JbOje GdeYdheGJ GdJj jecf Cf jJYdegG GdeJYde Yf WQjb GdeWGdYI hGdJacjQ, cCMcGe Gdhba hGdGHJOGA (B((3GdJj JTO eJYde JLhjO GdCOGA Edi JOHQ eYGfj BjGJ QHg SHMGfg MJi jMSf Gdhba(B)(3, heQJHG CMcGe JLhjO GdCOGA, HGdHOA HeG jSgd Ydi GdbGQF ageg HOhf eTGagI, hGdJOQL ef GdCSgd Edi GdSgd, hJCNjQ eG jJWdH GdJdbj HGdeTGagI(B.. (3hPdc dGNJUGQ GdhbJ hGdLgO Ydi GdeJYde hGdeYde(B. (3ajYQa HGdJQJjd, hJLhjO GdCOGA, hBOGH JdGhI GdbQBf GdbdHjI hGdXGgQjI, hPcQ ajg eYdheGJ YGeI ef GdJQJjd, hJLhjO GdCOGA, hYde GdJLhjO, hYde GdbQGAGJ, hGdJYQja HGddMf GdLdj hGddMf GdNaj, heaghe GdMQcGJ GdKdGK cjajI fWbgG, heQGJH GdJdGhI, hCSGdjH GdJdGhI ZjQ GdLGFRI(B. s
Keywords: (3GdbQBfs -- (3JLhjOs; (3GdbQBfs -- (3bQGAGJs